Knowledge and Attitude of Beef Cattle Farmers Towards Adoption of Crop Residu Technology for Animal Feeding - V. S. Lestari; D. P. Rahardja; M. B. Rombe (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2015)
This study was conducted using 24 beef cattle farmers which were choosen through purposive sampling. The aim of this research was to know the level of knowledge and attitude of beef cattle farmers and constraints towards adoption of crop residu technology for animal feeding in Sinjai Regency, South Sulawesi Province. The study revealed that the majority of beef cattle famers (75%) had moderate level of knowledge and favourable attitude (83,3%) towards adoption of crop residu technology for animal feeding. The major contraints in adopting the technology were lack of inputs, capital, labour, knowledge, and motivation. Collaboration among beef cattle farmers as stake holders, local animal husbandry service, extension workers and financial institution support is definitely required.